Alkali metal cation cooperative iodide anion recognition by new heteroditopic bis(calix[4]arene) rhenium(I) bipyridyl receptor molecules - Beer, P; Cooper, J (1998)
New heteroditopic bis(calix[4]arene) rhenium(I) bipyridyl receptors are synthesised and shown to simultaneously bind alkali metal cations and iodide anion with positive cooperativity.